2018
DOI: 10.2146/ajhp160760
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach to vancomycin level monitoring: Impact of a multidisciplinary monitoring system on timing of vancomycin levels

Abstract: A novel multidisciplinary approach to vancomycin trough monitoring involving automatic generation of trough orders, pharmacist validation of trough orders, and inclusion of trough orders in the nursing medication administration record was successful in significantly improving timing of vancomycin trough levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…A total of 1043 plasma vancomycin concentrations were collected; 939 (90%) during intermittent infusions and 104 (10%) during continuous infusions. A median (range) of 5 1–36 vancomycin concentrations were obtained in each course of therapy, collections occurring every 1.6 days (0.6–8 days).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1043 plasma vancomycin concentrations were collected; 939 (90%) during intermittent infusions and 104 (10%) during continuous infusions. A median (range) of 5 1–36 vancomycin concentrations were obtained in each course of therapy, collections occurring every 1.6 days (0.6–8 days).…”
Section: Resultsmentioning
confidence: 99%
“…Poorly timed sample collection is welldocumented in the clinical environment; only 20-59% of all TDM samples collected are trough concentrations. 8,12,16,32,33 Alternative approaches, such as Bayesian forecasting, that enable estimation of drug exposure from opportunistically collected samples are advocated, where available, to avoid misinterpretation of inappropriately timed collections, in addition to enabling optimal dosing. 34 Consistent with audits of other antimicrobials, 35 and perhaps most concerning, 44% of trough concentrations identified in the audit warranted dose adjustment according to guidelines, but were not acted upon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that developing simple auto‐text tools improved the productivity of pharmacists when working with EMR systems. This is reflective of an increase in pharmacist involvement in TDM in our study 7,10 …”
Section: Discussionmentioning
confidence: 67%
“…9 Erroneously timed trough blood draw was significantly affecting the quality of the TDM process and solutions have been proposed to improve it. 7,10,11 However, little was known about the timing issue associated with other steps involved in IV vancomycin administration, despite that IV infusion administration is an error prone process.…”
Section: Background and Significancementioning
confidence: 99%